New Materials for Thermoelectric Applications: Theory and Experiment - Zlatic, Veljko; Hewson, Alex.; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2013)
Thermoelectric devices could play an important role in making efficient use of our energy resources but their efficiency would need to be increased for their wide scale application. There is a multidisciplinary search for materials with an enhanced thermoelectric responses for use in such devices. This volume covers the latest ideas and developments in this research field, covering topics ranging from the fabrication and characterization of new materials, particularly those with strong electron correlation, use of nanostructured, layered materials and composites, through to theoretical work to gain a deeper understanding of thermoelectric behavior. It should be a useful guide and stimulus to all working in this very topical field.
Keywords: Physics; Physics; Condensed Matter Physics; Nanoscale Science and Technology; Solid State Physics; Strongly Correlated Systems, Superconductivity